Web-Based Flood Hazard Monitoring - Anna Nur Nazilah Chamim; Dwi Cahyo Hardyanto; Karisma Trinanda Putra (Journal of Robotics and Control (JRC), 2021)
Flood is a natural disaster. It occurs in several cities in Indonesia. Floods caused by rivers that overflowed and then flooded residential areas. It comes mostly unexpectedly without early warning. It causes many losses, especially the loss of material, and health threats to surrounding communities. The advance of network technology can reduce the adverse effects of flooding by providing warning alarms and water level monitoring system in real-time that can be accessed via the web. Based on the problem, a monitoring system was designed to monitor water levels via a web that work in real time for 24 hours, and store water level data into the database. The use of this website requires an internet connection, so that internet services must be available.